Edukasi kepada Anak-anak SMP Muhammadiyah 57 Medan mengenai Pemilahan Jenis Sampah - Nisaul Fadilah Dalimunthe; Gina Cynthia R Hasibuan (CERED Indonesia Publishing, 2022)
Waste is a common problem that is often found in the environment. One alternative that can be implemented to reduce the waste problem is by sorting waste based on its category. The purpose of waste sorting is to reduce waste accumulation, environmental pollution and to be able to reuse waste that still has economic value. The method applied in this community service is by implementing direct counselling and demonstration on the sorting of organic and inorganic waste types, which consists of several stages, namely: agreement, preparation of socialization or counselling and practical implementation of socialization / counselling and evaluation. From the results of the community service activity, all questions could be answered by the participants. Each participant can categorize waste based on its category and know the importance of sorting waste. With this community service activity, every student is expected not only to apply it in the school environment but also in the community.